Recent Advances in Hydroxyapatite Scaffolds Containing Mesenchymal Stem Cells - John Michel; Matthew Penna; Juan Kochen; Herman Cheung (Stem Cells International)
Modern day tissue engineering and cellular therapies have gravitated toward using stem cells with scaffolds as a dynamic modality to aid in differentiation and tissue regeneration. Mesenchymal stem cells (MSCs) are one of the most studied stem cells used in combination with scaffolds. These cells differentiate along the osteogenic lineage when seeded on hydroxyapatite containing scaffolds and can be used as a therapeutic option to regenerate various tissues. In recent years, the combination of hydroxyapatite and natural or synthetic polymers has been studied extensively. Due to the interest in these scaffolds, this review will cover the wide range of hydroxyapatite containing scaffolds used with MSCs for in vitro and in vivo experiments. Further, in order to maintain a progressive scope of the field this review article will only focus on literature utilizing adult human derived MSCs (hMSCs) published in the last three years.